Analysing breast cancer survivors’ acceptance profiles for using an electronic pillbox connected to a smartphone application using Seintinelles, a French community-based research tool - Goetzinger, Catherine; Alleaume, Caroline; Schritz, Anna; Vrijens, Bernard; Préau, Marie; Fagherazzi, Guy; Huiart, Laetitia (Frontiers in Pharmacology, 2022)
Introduction Up to 50% of breast cancer (BC) survivors discontinue their adjuvant endocrine therapy (AET) before the recommended five years, raising the issue of medication non-adherence. eHealth technologies have the potential to support patients to enhance their medication adherence and may offer an effective way to complement healthcare. In order for eHealth technologies to be successfully implemented into the healthcare system, end-users need to be willing and accepting to use these eHealth technologies. Aim This study aims to evaluate the current usability of eHealth technologies in BC survivors and to identify differences in BC survivors accepting a medication adherence enhancing eHealth technology to support their AET to BC survivors that do not accept such a medication adherence enhancing eHealth technology. Methods This study was conducted in 2020 including volunteering BC survivors from the Seintinelles Association. Eligible participants were women diagnosed with BC within the last 10 years, and been exposed to AET. Univariable and multivariable logistic regression analyses were performed to investigate medication adherence enhancing eHealth technology acceptance profiles among BC survivors. The dependent variable was defined as acceptance of an electronic pillbox connected to a smartphone application (hereafter: medication adherence enhancing eHealth technology) Results Overall, 23% of the participants already use a connected device or health application on a regular basis. The mean age of the participants was 52.7 (SD 10.4) years. In total, 67% of 1268 BC survivors who participated in the survey declared that they would accept a medication adherence enhancing eHealth technology to improve their AET. BC survivors accepting a medication adherence enhancing eHealth technology for their AET, are younger (OR=0.97, 95% CI [0.95; 0.98]), do take medication for other diseases (OR=0.31, 95% CI [0.13; 0.68]), already use a medication adherence enhancing eHealth technology or technique (OR=1.74, 95% CI [1.06; 2.94]) and are willing to possess or currently possess one or more connected devices or health applications (OR=2.89, 95% CI [2.01; 4.19]). Conclusion Understanding acceptance profiles of BC survivors is fundamental for conceiving an effective eHealth technology enhancing AET among BC survivors. Hence, such profiling will foster the development of personalized medication adherence enhancing eHealth technology.